2013
DOI: 10.1096/fj.13-234997
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid induces vasodilation mediated by LPA 1 receptors, phospholipase C, and endothelial nitric oxide synthase

Abstract: Lysophosphatidic acid (LPA) has been implicated as a mediator of several cardiovascular functions, but its potential involvement in the control of vascular tone is obscure. Here, we show that both LPA (18:1) and VPC31143 (a synthetic agonist of LPA1-3 receptors) relax intact mouse thoracic aorta with similar Emax values (53.9 and 51.9% of phenylephrine-induced precontraction), although the EC50 of LPA- and VPC31143-induced vasorelaxations were different (400 vs. 15 nM, respectively). Mechanical removal of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 72 publications
4
35
0
Order By: Relevance
“…An early report, using a piglet model of intracranial hematoma demonstrated that LPA exposure produces dose-dependent vasoconstriction, which is reminiscent of that produced by hemorrhage (Tigyi et al, 1995). More recently, LPA has been found to mediate vasodilation via LPA 1 , phospholipase C, and endothelial nitric oxide synthase (Ruisanchez et al, 2014). LPA overexposure has been reported to increase BBB permeability (On et al, 2013; Yu et al, 2014), as may occur during pathological conditions like stroke.…”
Section: Lparsmentioning
confidence: 99%
“…An early report, using a piglet model of intracranial hematoma demonstrated that LPA exposure produces dose-dependent vasoconstriction, which is reminiscent of that produced by hemorrhage (Tigyi et al, 1995). More recently, LPA has been found to mediate vasodilation via LPA 1 , phospholipase C, and endothelial nitric oxide synthase (Ruisanchez et al, 2014). LPA overexposure has been reported to increase BBB permeability (On et al, 2013; Yu et al, 2014), as may occur during pathological conditions like stroke.…”
Section: Lparsmentioning
confidence: 99%
“…Interestingly, increased LPA levels can rapidly and reversibly increase blood brain barrier permeability (80), suggesting a concentration-dependent mechanism. Finally, LPA can also regulate vascular tone, such as posthemorrhagic vasoconstriction in cerebral microvasculature (81) or vasodilation in the thoracic aorta (82). These opposing actions may be context dependent.…”
Section: Atxmentioning
confidence: 99%
“…53 Micromolar levels of LPA may induce a vasoconstrictive response 54 in medial SMCs under high shear stresses, but lower doses cause endothelium-dependent vasodilation via endothelial nitric oxide synthase and phospholipase activity. 55 VEGF is perhaps the most widely studied proangiogenic molecule whose activity has been targeted as a therapeutic for initiating neovascularization and for blocking tumor growth. S1P has also been touted as a complete angiogenic molecule given its contributions at both early stages of angiogenesis and later stages of neovessel stabilization.…”
Section: Figmentioning
confidence: 99%